Awareness of Patient Rights and Practice at Fayoum University Hospital - Safaa Khamis Hassan1 , Marwa Ali Mwaheb2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Patient rights are essential pillars to provide good health care and to promote ethical medicalpractices. Aim of work: to understand the perspectives of Fayoum patients’ on patients’ rights in thegovernment-run teaching hospitals of Fayoum University of Medical Sciences Method: A cross-sectionaldescriptive study was carried out at the inpatient wards of Fayoum University Hospital, Fayoum Governorate,Egypt. The study was conducted over four months from July to November 2019 Results: Only (21.8%)heard about patients’ rights. The knowledge score was significantly higher among; the working patient,those who heard or read about the patients’ rights and patients admitted in surgical sections (p-value =0000).Conclusion: Regarding the awareness and practice of the patients’ rights among the patients in Fayoumuniversity hospital there was a lake of knowledge. Only 42.34% of the patients were of good knowledge.